Application of Electrical Resistivity Tomography Technique for Characterizing Leakage Problem in Abu Baara Earth Dam, Syria - Walid Al-Fares (International Journal of Geophysics, 2014)
Electrical Resistivity Tomography (ERT) survey was carried out at Abu Baara earth dam in northwestern Syria, in order to delineate potential pathways of leakage occurring through the subsurface structure close to the dam body. The survey was performed along two straight measuring profiles of 715 and 430 m length in up- and downstream sides of the dam’s embankment. The analysis of the inverted ERT sections revealed the presence of fractured and karstified limestone rocks which constitute the shallow bedrock of the dam reservoir. Several subsurface structural anomalies were identified within the fractured bedrock, most of which are associated with probable karstic cavities, voids, and discontinuity features developed within the carbonates rocks. Moreover, results also showed the occurrence of a distinguished subsiding structure coinciding with main valley course. Accordingly, it is believed that the bedrock and the other detected features are the main potential causes of water leakage from the dam’s reservoir.